Ease-of-Use and User-Friendliness of Cloud Computing Adoption for Web-Based Services in Academic Libraries in Kwara State, Nigeria. Issue 3 (2nd November 2020) - Kayode, Adeniyi Isaiah; Tella, Adeyinka; Akande, Samson Oyeniyi
Abstract: This study examined ease-of-use, user-friendliness, and cloud computing adoption for Web-based service in academic libraries in Kwara State, Nigeria. Specifically, the study identified the types of cloud computing adopted for delivering Web-based services; examined the user-friendliness of cloud computing; identified the benefits of cloud computing; examined the ease-of-use of cloud computing and established the relationship between ease-of-use and user-friendliness and adoption of cloud computing for delivering Web-based services; and identify the challenges encountered by academic libraries in their adoption of cloud computing for delivering Web-based services. The study adopted a survey design using a sample of thirty-five (35) librarians drawn through the total enumeration method from three universities in Ilorin, Kwara State. Data were collected through a questionnaire and collected data were analyzed using frequency count and percentages. The hypotheses of the study were tested using the Pearson Product Moment Correlation (PPMC). The findings demonstrate that respondents confirmed the ease-of-use and user-friendliness of cloud computing for delivering Web-based services in academic libraries. The findings also reveal that cloud computing is flexible and not vulnerable to computer breakdowns and loss of data; easy to integrate existing work with the cloud-based services, saves time, and enables the accomplishment of tasks more quickly. The study recommends based on the findings that academic libraries should be provided with a reliable source of powers as backup against epileptic power supply with a strong Internet connection and broad bandwidth to further support the adoption of cloud computing in academic libraries in Kwara State, Nigeria.